SEÑALES DE ALARMA Y LA IMPORTANCIA DE SU CONOCIMIENTO EN MUJERES EMBARAZADAS - Balderrama Espinoza, Sara Imelda (2022)
https://www3.ugto.mx/redicinaysa/images/publicaciones/2022/REDICINAYSA-VOL.-11-NO.-3-MAYO-JUNIO-2022.pdf